Steroid hormone influence on melanomagenesis. (5th December 2015) - Mitkov, Mario; Joseph, Richard; Copland, John
Abstract: Disparities in the prognosis and incidence of melanoma between male and female patients have led clinicians to explore the influence of steroid hormones on the development and progression of this malignancy. A better understanding of the disparities of melanoma behavior between sexes and ages could lead to improved prevention and treatment options. There are multiple themes in the literature that unify the physiologic functions of estrogen and androgen receptors; herein we discuss and map their pathways. Overall, it is important to understand that the differences in melanoma behavior between the sexes are multifactorial and likely involve interactions between the immune system, endocrine system, and environment, namely UV-radiation. Melanoma deserves a spot among hormone-sensitive tumors, and if tamoxifen is re-introduced for future therapy, tissue ratios of estrogen receptors should be obtained beforehand to assess their therapeutic predictive value. Because androgens, estrogens, and their receptors are involved in signaling of commonly mutated melanoma pathways, potential synergistic properties of the recently developed molecular kinase inhibitors that target those pathways may exist. Highlights: Malignant melanoma should hold a place among the hormone sensitive malignancies. Interactions between ER/AR and UVR drive differential melanomagenesis between sexes. Steroid hormones can promote tumorgenesis through the MAPK and PI3K pathways. ERα:ERβ ratios can guide decision-making if tamoxifen is re-considered for melanoma therapy. Synergistic properties with antihormone and molecular kinase inhibitor therapy may exist.